Controversies in the Technical Aspects of ACL Reconstruction An Evidence-Based Medicine Approach - Nakamura, Norimasa; Zaffagnini, Stefano; Marx, Robert G.; Musahl, Volker; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book provides the reader with the best available evidence on the most pressing issues relating to reconstruction of the anterior cruciate ligament (ACL) with the goal of supporting surgical reconstruction of the ACL and improving outcomes for patients. Key topics for which evidence-based information is presented include selection of graft material and source, the use of different surgical techniques, graft rupture in relation to surgical technique, and progression to osteoarthritis. The book will aid the surgeon in making decisions with respect to fixation devices and tensioning, the bundles to be reconstructed, and whether to preserve remnants or partial bundle ruptures. An evidence-based stance is taken on evolving topics such as the anatomy of the tibial insertion site of the ACL and the role of the anterolateral capsule and posteromedial corner in high-grade rotatory instability. Furthermore, novel technical developments for measurement of knee laxity and soft tissue navigation are discussed. The reader will also find useful information on general issues concerning physical examination, arthroscopic setup, timing of reconstruction, anesthesia, and anticoagulation.
ACL prevention programs -- Arthroscopic set up for ACL reconstruction -- Early vs. delayed ACL reconstruction -- Physical examination for ACL injury -- Timing for pediatric ACL reconstruction -- Technical considerations for pediatric ACL reconstruction -- Anesthesia and nerve blocks for ACL reconstruction -- Anticoagulation after ACL reconstruction -- Technical considerations for patella tendon harvest -- Technical considerations for quadriceps tendon harvest -- Technical considerations for hamstring tendon harvest -- Meniscus repair with ACL reconstruction -- Anatomy of ACL insertion (Cadaveric & Histological study) -- Functional analysis of ACL insertion site -- How many bundles to be reconstructed? Single vs Double -- Femoral tunnel creation for anatomic ACL reconstruction -- Press fit graft fixation and bone grafting -- Is Notch plasty necessary for anatomic ACL reconstruction?- Pros and cons of different graft fixation device -- ACL graft tensioning -- ACL reconstruction for partial tear -- Remnant preservation in ACL reconstruction -- Allograft for ACL reconstruction -- Artificial ligament and Xeno-derived material for ACL reconstruction -- Extra articular plasty with ACL reconstruction -Long term results of associated procedure -- Treatment of MCL injury in combined ACL/MCL injury -- Treatment of ACL injury in the multi-ligament injured knee -- Anterolateral ligament repair/reconstruction combined to ACL reconstruction, rationale and technique -- Instrumental laxity evaluation (static) -- Instrumental laxity evaluation (dynamic) -- Evidence for use of navigation in ACL reconstruction -- Considerations for treatment of concomitant cartilage and ACL injury -- ACL reconstruction and progression of OA -- Re-rupture after ACL reconstruction -- Conservative treatment for ACL injury - When non op care is indicated -- Biplanar osteotomies in the ACL deficient knee -- Rehabilitation after ACL reconstruction.
Keywords: Medicine; Orthopedics; Rehabilitation; Sports medicine; Medicine & Public Health; Surgical Orthopedics; Rehabilitation; Sports medicine